Canada, John Forman [Foreman] at sign for Cape Breton Highlands National Park - Forman, Harrison, 1904-1978 (1959)
Canada - Cape Breton Known for its spectacular highlands and ocean scenery. Steep cliffs and deep river canyons carve into a forested plateau bordering the Atlantic Ocean.' Color Volume 199